MODERN CLASSIFICATION OF AUTIZM AND PSYCHO CORRECTIONAL WORK - Harutyunyan, A. K. (Modern Psychology, 2019)
The following article tries to generalize the immense material that is existent in a day by bay increasing disease such as autism. Through contradictory views, like some red thread, it goes between autism and schizophrenia - in one case, as between interconnected but different diseases, in the other case, as the main schizophrenia symptom. With the help of thousands of correctional meetings, as well as hundreds of examples of autistic children, here is presented the main clue, which is desirable to be known by beginner specialists, who are to work with children having such problems. The cooperation of a psychologist, a special pedagogue, a speech therapist and parent is beneficial in the rehabilitation work with the above mentioned children.